Tipologi migrasi: suatu alternatif pengembangan konsep - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
Abstract Using the migration survey done by Population Studies Center Gadjah Mada University, this article tries to find out the possibility in improving the definition of migration. It is based on the idea that migration is a process. It means that migration can be defined more than dichotomy of the concept of permanent and sirculation. The reason is that the dichotomy tends to ignore the possibility of migrants occupying one or more categories intermediate to the two polar types. By introducing the variable of intention to remain at the destination and the length of migrants stay in the destination, a fourfold typology of migrant type can be created: circular migrants, migrants who intend to remain circular, migrants who intend to be permanent and permanent migrants.